Marketing Opportunities In The Digital Economy - Bhatia, Swati; Abhishek, Anand (Gyan Management Journal, 2024)
Introduction: The Digital Economy refers to a collection of economic  and commercial activities that utilize digital technologies and electronic  communications. This type of economy typically includes various sectors and  activities such as e-commerce, digital marketing, digital financial services,  digital content production, software, computer games, cloud services etc. Focus of Research: This abstract provides a concise overview of the  research paper on “Marketing Opportunities in the Digital Economy.” The  paper explores the various marketing opportunities that have emerged  in the digital economy, driven by advancements in technology and the  increasing reliance on digital platforms.  It analyzes the strategies and techniques employed by businesses to reach  and engage with their target audience in this digital landscape. The abstract  also highlights the impact of the digital economy on consumer behavior  and the implications for marketers. The findings of this research offer  valuable insights for businesses seeking to capitalize on the marketing  opportunities presented by the digital economy. Objective: The objective of this research paper is to explore and analyze the  various marketing strategies and techniques that have emerged in the digital  economy. The paper aims to identify the benefits and challenges of digital  marketing, understand the impact of the digital economy on consumer  behavior, and provide insights and recommendations for businesses seeking  to capitalize on the marketing opportunities in the digital landscape. Learnings: The learnings from this study will contribute to a deeper  understanding of examining the digital economy and its impact on  businesses and users, as well as evaluating the opportunities for easy and  fast access to products and services that can lead to  increased efficiency and productivity.  It will provide  businesses with actionable insights to optimize their  digital marketing strategies and enhance their ability to  attract and retain customers in the digital age.
Keywords: businesses; audience; production; communications.; capitalize